Diz protezi rehabilitasyonunda farklı yöntemler - Geçer, Nuray (My University, 2002)
Bu çalışmada total diz protezi rehabilitasyonunda sürekli pasif hareket (SPH) cihazı ve proprioseptif nöromüsküler fasilitasyon (PNF) tekniğinin etkinliğinin karşılaştırılması amaçlanmıştır. Bu amaçla Marmara Üniversitesi Hastanesi Ortopedi nda total diz protezi cerrahisi geçirmiş 42 hasta çalışmamıza davet edilmiştir. Bu hastaların 30 tanesi rastgele yöntemle seçilerek iki gruba ayrılmışlardır. Birinci gruba SPH cihazı ve konvansiyonel tedavi, ikinci gruba PNF tekniği ve konvansiyonel tedavi uygulanmıştır. Hastalar hastanede kaldıkları süre içinde her gün, hastaneden çıktıktan sonra 2 ay haftada 3 kez, sonraki 2 ayda haftada 1 kez ayaktan tedavi ünitesine gelme şeklinde ve diğer günler ev eklinde verilen egzersizleri uygulamak koşulu ile 4 ay takip edilmişlerdir. Tüm hastalara rehabilitasyon süresi boyunca, 1, 2, 4, 8, 12 ve 16. haftalarda gonyometrik eklem hareket açıklığı ölçümleri (pasif ve aktif), ağrı, ruhsal değerlendirme, hastanede kalış günü, şişlik ölçümü, fonksiyonel değerlendirme skalası ile değerlendirme yapılmıştır. Dördüncü ayın sonunda ise izokinetik ve izometrik testler yapılmıştır. Hastalarımızın değerlendirme sonuçlarında; aktif olarak 45 ve 60 derece diz fleksiyonuna, pasif olarak da 45, 60, 90 ve 100 derece diz fleksiyonuna ulaşma günleri, ekstansiyon ölçümleri, hastanede kalış günü, fonksiyonel değerlendirme skala sonuçları, şişlik ölçümü, ağrı, ruhsal durum değerlendirmesi ve izokinetik ölçümlerde her iki grup arasında istatistiksel olarak bir farklılık bulunamamıştır. Fakat PNF grubu hastalar daha erken dönemde yardımcı cihazlarla yürümeye başlamış ve daha çabuk aktif 90 derece diz fleksiyonu yapabilmişlerdir. Sonuç olarak PNF grubu hastalarımız istenilen fonksiyonel düzeye ve dereceye daha çabuk ulaşmışlardır. Bu bilginin dışında PNF tekniği uygulamasının SPH cihazına herhangi bir üstünlüğü bulunmamakta ancak SPH cihazı hastanın egzersize uyum sağlayamadığı durumlarda iş gücü ve zaman kazancı açısından büyük yarar sağlamaktadır. In this study it has been aimed to compare the efficiencies of continuous passive motion (SPH) device and proprioceptive neuromuscular facilitation (PNF) technique in the rehabilitation of total knee prosthesis. For this reason, 42 patients who had a total knee prosthesis surgery in the Orthopedics Department of the Marmara University Hospital have been invited to participate at our study. 30 of these patients have been randomly chosen and divided into two groups. SPH device and conventional treatment have been applied to the patients in the first group and PNF technique and conventional treatment have been applied to the patients in the second group. Patients have been examined every day during their stay at the hospital and then after they have left the hospital they have come to our outpatient clinic where they have been under examination three times per week for the first two months, and once per week for the second two months with the condition that the patients have to perform the exercises given to them as indoor activities during the days when they have not come to our clinic. For all the patients, a general evaluation has been performed in the 1st, 2nd, 4th, 8th, 12th and 16th weeks of the rehabilitation by the following techniques; goniometric joint motion distance evaluations (passive and active), pain tests, emotional tests, evaluation of scale, evaluation of staying time at the hospital, measurement of swollen joints and functional evaluation scale. At the end of the fourth month, isokinetic and isometric tests have been applied. According to the evaluation results, no statistical difference between the two groups has been found out in the tests applied, which are finding out the amount of time in which the patients have been able to perform knee flexion at 45 and 60 degrees and the number of days in which they have been able to perform passive knee flexion at 45, 60, 90 and 100 degrees, extension measurements, evaluation of number of days that the patients have stayed at our hospital, functional evaluation scale results, measurement of swollen joints, pain and emotional tests and iso-kinetic evaluations. But the patients in the PNF group have been able to begin to walk earlier with auxiliary devices and have performed knee flexion at 90 degrees more quickly than the patients in the other group. As a result, the patients in the PNF group have reached the desired functional level and degree more quickly. However PNF technique applied does not have any advantage over SPH device but it is a fact that SPH device saves labor force and time in such conditions where the patient can not adapt to performing exercises.
Keywords: Protezler